Socially responsible investment and financial performance of JSE listed companies in South Africa - Govender, Tamara (My University, 2016)
ABSTRACT This research report is on socially responsible investment (SRI) and financial performance of JSE listed companies in South Africa. The research methodology entails a quantitative study, obtaining secondary data on SRI compliance and financial metrics of JSE SRI constituents listed from 2012 – 2014. The final sample size was 62 companies across nine industrial sectors. The research instrument was a specially developed 30 point SRI scorecard encompassing the environmental, social, governance and climate categories based on the criteria of the SRI Index. Reviewing annual and or sustainability development reports from the public domain, each company was then rated on a three point rating scale for evidence of compliance to the scorecard. Financial data for JSE companies and JSE indices included price to earnings, price to book value and closing share prices were obtained from the INET BFA database. It was found that there is a negative correlation with the mean SRI score and the overall annual share price return and price to book value whilst there is a positive correlation with price to earnings ratio. Furthermore there was no significant improvement in the SRI scores from 2012 to 2014 and only the governance and related sustainability concerns category showed a significant change which was positive. In terms of the propositions, the finding is that JSE listed companies with high SRI scores achieved higher than average return over two years in only the health care and industrials sectors. Secondly JSE listed companies with low SRI scores achieved lower than average return over two years in only the consumer services and financials sectors. Lastly JSE listed companies with high SRI scores achieved higher company valuation than companies with low company valuation in the consumer goods and industrials sectors out of nine industrial sectors. Thus the results are inconsistent in both propositions. The findings from this research demonstrate that there is inconsistent financial performance when investing in SRI companies listed on the JSE Index and is thus consistent with the related literature.
MBA Thesis
Keywords: Johannesburg Stock Exchange, Investments -- Social aspects, Social responsibility of business, Stocks -- Prices -- South Africa.